Cultural studies : theory and practice - Barker, Chris, 1955- (Los Angeles ; London : SAGE, 2012)
This comprehensive, self-contained introduction to the theory, practice and core issues of cultural studies focuses on particular issues of contemporary interest, including ideology, language, gender, race and identity.
Ch. 1. An Introduction to Cultural Studies -- Ch. 2. Questions of Culture and Ideology -- Ch. 3. Culture, Meaning, Knowledge: The linguistic Turn in Cultural Studies -- Ch. 4. Biology, The Body and Culture -- Ch. 5. A New World Disorder? -- Ch. 6. Enter Postmodernism -- Ch. 7. Issues of Subjectivity and Identity -- Ch. 8. Ethnicity, Race and Nation -- Ch. 9. Sex, Subjectivity and Representation -- Ch. 10. Television, Texts and Audiences -- Ch. 11. Digital Media Culture -- Ch. 12. Cultural Space and Urban Place -- Ch. 13. Youth, Style and Resistance -- Ch. 14. Cultural Politics and Cultural Policy.
Includes bibliographical references (pages 514-536) and index.
Keywords: Culture -- Study and teaching; Culture; Culturele studies; Culture; Culture -- Study and teaching; Kulturwissenschaften; Culturele studies; Kulturstudier; Kulturwissenschaften; Lehrbuch